OpenAIREplus: supporting repository interoperability through guidelines - Príncipe, Pedro (2013)
Supporting the open access policy of the European Commission, OpenAIRE is moving from a publication infrastructure to a more comprehensive infrastructure that covers all types of scientific output, funded by the European Commission, and widening to other European funding streams. It harvests content from a range of European repositories, and ensures raised visibility of valuable open access content, as well as links to project and funding information. In order to ensure interoperability from these research infrastructures, a common approach is need to adhere to existing and future guidelines. In this context, an integrated suite of guidelines have been developed. The poster will briefly outline the OpenAIRE Guidelines: Guidelines for Data Archive Managers, for Literature Repository Managers and for CRIS Managers. By implementing all three sets of the OpenAIRE Guidelines, repository managers will be able to enable authors who deposit publications in their repository to fulfill the EC Open Access requirements, as well as the requirements of other (national or international) funders with whom OpenAIRE cooperates. In addition it will allow the OpenAIRE infrastructure to add value‐added services such as discoverability and linking, and creation of enhanced publications. In short, building the stepping‐stones for a linked data infrastructure for research.